2020
DOI: 10.1101/2020.06.18.137471
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic analysis of REBASE identifies numerous Type I restriction-modification systems that contain duplicated, variablehsdSspecificity genes that randomly switch methyltransferase specificity by recombination

Abstract: that contain duplicated, variable hsdS specificity genes that randomly switch 2 methyltransferase specificity by recombination. 3 4 5 Abstract 29 N 6 -adenine DNA methyltransferases associated with some Type I and Type III restriction-30 modification (R-M) systems are able to randomly switch expression by variation in the length of 31 locus-encoded simple sequence repeats (SSRs). SSR tract-length variation causes ON/OFF 32 switching of methyltransferase expression, resulting in genome-wide methylation differen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In contrast to previously characterized phase-variable Type I RM systems, we demonstrate that additional hsdS alleles further downstream of hsdM are not always silent. To the best of our knowledge, in all phase-variable Type I RM systems described so far, only the hsdS allele directly downstream of the hsdM is transcribed and involved in genome methylation (10,13,26,27,30,31,34). Therefore, it was suggested that the other TRDs or hsdS within the locus are merely present to function as DNA templates for recombination (34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to previously characterized phase-variable Type I RM systems, we demonstrate that additional hsdS alleles further downstream of hsdM are not always silent. To the best of our knowledge, in all phase-variable Type I RM systems described so far, only the hsdS allele directly downstream of the hsdM is transcribed and involved in genome methylation (10,13,26,27,30,31,34). Therefore, it was suggested that the other TRDs or hsdS within the locus are merely present to function as DNA templates for recombination (34).…”
Section: Discussionmentioning
confidence: 99%
“…S5A) (8), thus we speculate that SsuPORF1588P is not functional in methylation. SsuPORF1273P is phase-variable (26) and the methylation profile of its two dominant alleles (A and B) has been solved by SMRT sequencing of E. coli overexpressing the S. suis methyltransferases, giving CC m6 AN 8 CTT for allele A and CC m6 AN 6 DNH (D=A/G/T, H=A/C/T and N=A/C/G/T) for allele B (27). SsuPORF1273P expression when grown overnight on BHI plate has been demonstrated, but genome methylation in S. suis has not been shown yet (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation